2010
DOI: 10.2217/fnl.10.79
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in rehabilitation interventions for visual neglect and anosognosia for hemiplegia following right hemisphere stroke

Abstract: This article highlights the most recent findings regarding the rehabilitation interventions for the syndromes of visual neglect and anosognosia for hemiplegia that occur following right hemisphere stroke. We review papers published in the past 4 years pertaining to therapeutic approaches for these two syndromes in order to identify the trends in the development of effective interventions.Overall, it appears well recognized that visual neglect syndromes and awareness syndromes frequently co-occur and both inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…Future research is required to replicate these findings and to determine if they are generalizable to other neuropsychiatric disorders that may exhibit impaired clinical or cognitive insight. Noninvasive techniques, including transcranial magnetic, direct current or caloric vestibular stimulation—shown to induce spatial hemineglect in healthy controls, transiently reverse anosognosia in right hemisphere damaged stroke patients, and improve clinical insight in schizophrenia spectrum and bipolar disorders (Cappa et al, 1987; Oliveri et al, 2001; Miller and Ngo, 2007; Sparing et al, 2009; Kortte and Hillis, 2011; Levine et al, 2012), can be used to further investigate the theory of interhemispheric imbalance of clinical insight in schizophrenia spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Future research is required to replicate these findings and to determine if they are generalizable to other neuropsychiatric disorders that may exhibit impaired clinical or cognitive insight. Noninvasive techniques, including transcranial magnetic, direct current or caloric vestibular stimulation—shown to induce spatial hemineglect in healthy controls, transiently reverse anosognosia in right hemisphere damaged stroke patients, and improve clinical insight in schizophrenia spectrum and bipolar disorders (Cappa et al, 1987; Oliveri et al, 2001; Miller and Ngo, 2007; Sparing et al, 2009; Kortte and Hillis, 2011; Levine et al, 2012), can be used to further investigate the theory of interhemispheric imbalance of clinical insight in schizophrenia spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in the introduction, there have been recent advances in the management of AHP by providing specific rehabilitation guidelines and strategies (see Jenkinson et al, 2011 andMorrene-Stupinsky, 2010, for reviews), with temporary remission of AHP also recently being reported using a combination of techniques (see Beschin et al, 2012). Unfortunately, despite these rehabilitation efforts, there is currently no known, efficacious intervention for permanent restoration of motor awareness in patients with AHP (Kortte & Hills, 2011;Jenkinson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…7 I also predict continued growth in the clinical community's understanding of complex conditions and of less conventional treatment options. Knowledge of the diversity and many facets of disorders that have significant consequences for patient outcomes, like neglect and anosognosia, 8 will become more common, along with an awareness of the wealth of treatment possibilities for these impairments. 1,8 The multiple techniques developed to address neglect, for example, including several elaborated in the Emerging Technologies section that follows, have gone far beyond the time-worn exhortations for the patient to "look to the left" or putting a red line on the left side of a page.…”
Section: Approaching Their Managementmentioning
confidence: 99%
“…Knowledge of the diversity and many facets of disorders that have significant consequences for patient outcomes, like neglect and anosognosia, 8 will become more common, along with an awareness of the wealth of treatment possibilities for these impairments. 1,8 The multiple techniques developed to address neglect, for example, including several elaborated in the Emerging Technologies section that follows, have gone far beyond the time-worn exhortations for the patient to "look to the left" or putting a red line on the left side of a page. 1,8 I predict that speech-language clinicians will be better versed in these newer techniques and more credibly bring their talents to multidisciplinary treatment teams as a result.…”
Section: Approaching Their Managementmentioning
confidence: 99%
See 1 more Smart Citation